Use the Six Sigma technique in a solutionProblems of work (analytical study) - الطائي علي حسون; نايف اسعد كاظم (Journal of Economics and Administrative Sciences, 2009)
The research Concentrates on modern Variable in the organizations that is 6 sigma. The field study is two of Iraqi industrial organizations, The first is state company of …………… , the other is the state company of …… The problem of the research determines some questions and hypotheses, The data was Collected by question air, which contains 5 dimensions and (10) critical Successful factories . The sample contains (42) who Works in that organizations. The points out many conclusions. The main of it, there is significant differences among the two organizations Then The research concluded with a number of important recommendations serve it’s objectives .